PROFESIONALITAS KEPEMIMPINAN PENDIDIKAN DALAM MEMAHAMI PERAN DAN FUNGSI PIMPINAN LEMBAGA - Aulia Sinta Rahmawati; Rania Salsabila Sa’i; Serena Aulia Hamid; Zefania Safarina Fadilah; Mardiyah Mardiyah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Educational leadership is a key factor in determining the quality and success of an educational institution. In the context of increasingly complex modern devlopments, educational leaders are required to demonstrate a high level of professional quality in understanding and implementing their roles and functions effectively. This study aims to analyza the professional quality of educational leadership in understanding the roles and functions of institutional leaders and its implications for improving educational quality. This research employs a descriptive qualitative approach using a literature study method by examining various academic sources such as book, journals, and relevant documents related to educational leadership and management. The data were analyzed systematically to obtain a comprehensive understanding of the concept of professional educational leadership quality. The reults indicate that professional quality in educational leadership encompasses various competencies, including managerial, personal, social, and professional competencies. Educational leaders serve multiple roles, such as leaders, managers, educators, administrators, and supervisors, which must be carried out in an integrated manner. In addition, leadders perform key management functions, namely planning, organizing, actuating, and controlling. Professional quality in leadership is not only oriented toward technical abilities but also toward integrity, responsibility, and exemplary behavior. In conclusion, the professional quality of educational leadership significantly influences the effectiveness of institutional management and the overall improvement of educational quality. Therefore, educational leaders need to continuously develop their competencies and personal qualities to face the challenges of modern education..